INTERNATIONAL THEATRICAL EDUCATIONAL PROGRAM: 25 YEARS OF EXPERIENCE IN MOSCOW ART THEATRE SCHOOL - Elena Viktorovna Burdenko; Irina I ARTSIS; Natalia Stepanovna ILYUSHCHENKO (Высшее образование в России)
In the article is concerned with the research results regarding the creation, development and implementation of the international theatrical educational program organized by the Moscow Art Theatre School together with the Eugene O'Neill Theatre Centre. Emphasis is placed on the related parts of the international theatrical educational programs, which enable foreign students to achieve full development of professional knowledge and skills. The results obtained confirm the necessity of carrying out international theatrical educational programs which is facilitated by the ongoing rise in global student mobility.